Runtime Complexity TRS:
The TRS R consists of the following rules:

minus(x, 0) → x
minus(s(x), s(y)) → minus(x, y)
quot(0, s(y)) → 0
quot(s(x), s(y)) → s(quot(minus(x, y), s(y)))
plus(0, y) → y
plus(s(x), y) → s(plus(x, y))
minus(minus(x, y), z) → minus(x, plus(y, z))
app(nil, k) → k
app(l, nil) → l
app(cons(x, l), k) → cons(x, app(l, k))
sum(cons(x, nil)) → cons(x, nil)
sum(cons(x, cons(y, l))) → sum(cons(plus(x, y), l))
sum(app(l, cons(x, cons(y, k)))) → sum(app(l, sum(cons(x, cons(y, k)))))
plus(s(x), s(y)) → s(s(plus(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
plus(s(x), x) → plus(if(gt(x, x), id(x), id(x)), s(x))
plus(zero, y) → y
plus(id(x), s(y)) → s(plus(x, if(gt(s(y), y), y, s(y))))
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
gt(s(x), zero) → true
gt(zero, y) → false
gt(s(x), s(y)) → gt(x, y)

Rewrite Strategy: INNERMOST

Renamed function symbols to avoid clashes with predefined symbol.

Runtime Complexity TRS:
The TRS R consists of the following rules:

minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Rewrite Strategy: INNERMOST

Infered types.

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Heuristically decided to analyse the following defined symbols:
minus', quot', plus', app', sum', gt'

They will be analysed ascendingly in the following order:
minus' < quot'
plus' < minus'
plus' < sum'
gt' < plus'
app' < sum'

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

The following defined symbols remain to be analysed:
app', minus', quot', plus', sum', gt'

They will be analysed ascendingly in the following order:
minus' < quot'
plus' < minus'
plus' < sum'
gt' < plus'
app' < sum'

Proved the following rewrite lemma:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)

Induction Base:
app'(_gen_nil':cons'4(0), _gen_nil':cons'4(b)) →RΩ(1)
_gen_nil':cons'4(b)

Induction Step:
app'(_gen_nil':cons'4(+(_\$n7, 1)), _gen_nil':cons'4(_b253)) →RΩ(1)
cons'(0', app'(_gen_nil':cons'4(_\$n7), _gen_nil':cons'4(_b253))) →IH
cons'(0', _gen_nil':cons'4(+(_\$n7, _b253)))

We have rt ∈ Ω(n) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Lemmas:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

The following defined symbols remain to be analysed:
gt', minus', quot', plus', sum'

They will be analysed ascendingly in the following order:
minus' < quot'
plus' < minus'
plus' < sum'
gt' < plus'

Proved the following rewrite lemma:
gt'(_gen_0':s':zero':true':false'3(+(1, _n1608)), _gen_0':s':zero':true':false'3(+(1, _n1608))) → _*5, rt ∈ Ω(n1608)

Induction Base:
gt'(_gen_0':s':zero':true':false'3(+(1, 0)), _gen_0':s':zero':true':false'3(+(1, 0)))

Induction Step:
gt'(_gen_0':s':zero':true':false'3(+(1, +(_\$n1609, 1))), _gen_0':s':zero':true':false'3(+(1, +(_\$n1609, 1)))) →RΩ(1)
gt'(_gen_0':s':zero':true':false'3(+(1, _\$n1609)), _gen_0':s':zero':true':false'3(+(1, _\$n1609))) →IH
_*5

We have rt ∈ Ω(n) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Lemmas:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)
gt'(_gen_0':s':zero':true':false'3(+(1, _n1608)), _gen_0':s':zero':true':false'3(+(1, _n1608))) → _*5, rt ∈ Ω(n1608)

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

The following defined symbols remain to be analysed:
plus', minus', quot', sum'

They will be analysed ascendingly in the following order:
minus' < quot'
plus' < minus'
plus' < sum'

Proved the following rewrite lemma:
plus'(_gen_0':s':zero':true':false'3(_n4232), _gen_0':s':zero':true':false'3(b)) → _gen_0':s':zero':true':false'3(+(_n4232, b)), rt ∈ Ω(1 + n4232)

Induction Base:
plus'(_gen_0':s':zero':true':false'3(0), _gen_0':s':zero':true':false'3(b)) →RΩ(1)
_gen_0':s':zero':true':false'3(b)

Induction Step:
plus'(_gen_0':s':zero':true':false'3(+(_\$n4233, 1)), _gen_0':s':zero':true':false'3(_b4783)) →RΩ(1)
s'(plus'(_gen_0':s':zero':true':false'3(_\$n4233), _gen_0':s':zero':true':false'3(_b4783))) →IH
s'(_gen_0':s':zero':true':false'3(+(_\$n4233, _b4783)))

We have rt ∈ Ω(n) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Lemmas:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)
gt'(_gen_0':s':zero':true':false'3(+(1, _n1608)), _gen_0':s':zero':true':false'3(+(1, _n1608))) → _*5, rt ∈ Ω(n1608)
plus'(_gen_0':s':zero':true':false'3(_n4232), _gen_0':s':zero':true':false'3(b)) → _gen_0':s':zero':true':false'3(+(_n4232, b)), rt ∈ Ω(1 + n4232)

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

The following defined symbols remain to be analysed:
minus', quot', sum'

They will be analysed ascendingly in the following order:
minus' < quot'

Proved the following rewrite lemma:
minus'(_gen_0':s':zero':true':false'3(+(1, _n6253)), _gen_0':s':zero':true':false'3(+(1, _n6253))) → _*5, rt ∈ Ω(n6253)

Induction Base:
minus'(_gen_0':s':zero':true':false'3(+(1, 0)), _gen_0':s':zero':true':false'3(+(1, 0)))

Induction Step:
minus'(_gen_0':s':zero':true':false'3(+(1, +(_\$n6254, 1))), _gen_0':s':zero':true':false'3(+(1, +(_\$n6254, 1)))) →RΩ(1)
minus'(_gen_0':s':zero':true':false'3(+(1, _\$n6254)), _gen_0':s':zero':true':false'3(+(1, _\$n6254))) →IH
_*5

We have rt ∈ Ω(n) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Lemmas:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)
gt'(_gen_0':s':zero':true':false'3(+(1, _n1608)), _gen_0':s':zero':true':false'3(+(1, _n1608))) → _*5, rt ∈ Ω(n1608)
plus'(_gen_0':s':zero':true':false'3(_n4232), _gen_0':s':zero':true':false'3(b)) → _gen_0':s':zero':true':false'3(+(_n4232, b)), rt ∈ Ω(1 + n4232)
minus'(_gen_0':s':zero':true':false'3(+(1, _n6253)), _gen_0':s':zero':true':false'3(+(1, _n6253))) → _*5, rt ∈ Ω(n6253)

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

The following defined symbols remain to be analysed:
quot', sum'

Could not prove a rewrite lemma for the defined symbol quot'.

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Lemmas:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)
gt'(_gen_0':s':zero':true':false'3(+(1, _n1608)), _gen_0':s':zero':true':false'3(+(1, _n1608))) → _*5, rt ∈ Ω(n1608)
plus'(_gen_0':s':zero':true':false'3(_n4232), _gen_0':s':zero':true':false'3(b)) → _gen_0':s':zero':true':false'3(+(_n4232, b)), rt ∈ Ω(1 + n4232)
minus'(_gen_0':s':zero':true':false'3(+(1, _n6253)), _gen_0':s':zero':true':false'3(+(1, _n6253))) → _*5, rt ∈ Ω(n6253)

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

The following defined symbols remain to be analysed:
sum'

Proved the following rewrite lemma:
sum'(_gen_nil':cons'4(+(1, _n12047))) → _gen_nil':cons'4(1), rt ∈ Ω(1 + n12047)

Induction Base:
sum'(_gen_nil':cons'4(+(1, 0))) →RΩ(1)
cons'(0', nil')

Induction Step:
sum'(_gen_nil':cons'4(+(1, +(_\$n12048, 1)))) →RΩ(1)
sum'(cons'(plus'(0', 0'), _gen_nil':cons'4(_\$n12048))) →LΩ(1)
sum'(cons'(_gen_0':s':zero':true':false'3(+(0, 0)), _gen_nil':cons'4(_\$n12048))) →IH
_gen_nil':cons'4(1)

We have rt ∈ Ω(n) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

Rules:
minus'(x, 0') → x
minus'(s'(x), s'(y)) → minus'(x, y)
quot'(0', s'(y)) → 0'
quot'(s'(x), s'(y)) → s'(quot'(minus'(x, y), s'(y)))
plus'(0', y) → y
plus'(s'(x), y) → s'(plus'(x, y))
minus'(minus'(x, y), z) → minus'(x, plus'(y, z))
app'(nil', k) → k
app'(l, nil') → l
app'(cons'(x, l), k) → cons'(x, app'(l, k))
sum'(cons'(x, nil')) → cons'(x, nil')
sum'(cons'(x, cons'(y, l))) → sum'(cons'(plus'(x, y), l))
sum'(app'(l, cons'(x, cons'(y, k)))) → sum'(app'(l, sum'(cons'(x, cons'(y, k)))))
plus'(s'(x), s'(y)) → s'(s'(plus'(if'(gt'(x, y), x, y), if'(not'(gt'(x, y)), id'(x), id'(y)))))
plus'(s'(x), x) → plus'(if'(gt'(x, x), id'(x), id'(x)), s'(x))
plus'(zero', y) → y
plus'(id'(x), s'(y)) → s'(plus'(x, if'(gt'(s'(y), y), y, s'(y))))
id'(x) → x
if'(true', x, y) → x
if'(false', x, y) → y
not'(x) → if'(x, false', true')
gt'(s'(x), zero') → true'
gt'(zero', y) → false'
gt'(s'(x), s'(y)) → gt'(x, y)

Types:
minus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
0' :: 0':s':zero':true':false'
s' :: 0':s':zero':true':false' → 0':s':zero':true':false'
quot' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
plus' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
app' :: nil':cons' → nil':cons' → nil':cons'
nil' :: nil':cons'
cons' :: 0':s':zero':true':false' → nil':cons' → nil':cons'
sum' :: nil':cons' → nil':cons'
if' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
gt' :: 0':s':zero':true':false' → 0':s':zero':true':false' → 0':s':zero':true':false'
not' :: 0':s':zero':true':false' → 0':s':zero':true':false'
id' :: 0':s':zero':true':false' → 0':s':zero':true':false'
zero' :: 0':s':zero':true':false'
true' :: 0':s':zero':true':false'
false' :: 0':s':zero':true':false'
_hole_0':s':zero':true':false'1 :: 0':s':zero':true':false'
_hole_nil':cons'2 :: nil':cons'
_gen_0':s':zero':true':false'3 :: Nat → 0':s':zero':true':false'
_gen_nil':cons'4 :: Nat → nil':cons'

Lemmas:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)
gt'(_gen_0':s':zero':true':false'3(+(1, _n1608)), _gen_0':s':zero':true':false'3(+(1, _n1608))) → _*5, rt ∈ Ω(n1608)
plus'(_gen_0':s':zero':true':false'3(_n4232), _gen_0':s':zero':true':false'3(b)) → _gen_0':s':zero':true':false'3(+(_n4232, b)), rt ∈ Ω(1 + n4232)
minus'(_gen_0':s':zero':true':false'3(+(1, _n6253)), _gen_0':s':zero':true':false'3(+(1, _n6253))) → _*5, rt ∈ Ω(n6253)
sum'(_gen_nil':cons'4(+(1, _n12047))) → _gen_nil':cons'4(1), rt ∈ Ω(1 + n12047)

Generator Equations:
_gen_0':s':zero':true':false'3(0) ⇔ 0'
_gen_0':s':zero':true':false'3(+(x, 1)) ⇔ s'(_gen_0':s':zero':true':false'3(x))
_gen_nil':cons'4(0) ⇔ nil'
_gen_nil':cons'4(+(x, 1)) ⇔ cons'(0', _gen_nil':cons'4(x))

No more defined symbols left to analyse.

The lowerbound Ω(n) was proven with the following lemma:
app'(_gen_nil':cons'4(_n6), _gen_nil':cons'4(b)) → _gen_nil':cons'4(+(_n6, b)), rt ∈ Ω(1 + n6)